Treacher Collins syndrome: A case report and review of literature - Tarun Kumar; Gagan Puri; Aravinda Konidena; Neha Arora (Journal of Indian Academy of Oral Medicine and Radiology, 2015)
Treacher Collins syndrome (TCS) or Franceschetti syndrome is an autosomal dominant disorder of craniofacial development with variable expressivity. It is named after Treacher Collins who described the essential components of the condition in 1900. Incidence of this syndrome is approximately 1 in 50,000 live births and it affects both genders equally. It affects structures which are derivatives of the first and second brachial arches. The most common manifestations of TCS are the antimongoloid slanting of the palpebral fissures, colobomas of the lower eyelids, hypoplasia of zygoma and mandible, and various ear abnormalities. This article describes the clinical and radiographic features of TCS in an 18-month-old female who had reported to the Department of Oral Medicine and Radiology.